The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmolb.2021.634141
|View full text |Cite
|
Sign up to set email alerts
|

Review of Machine Learning Methods for the Prediction and Reconstruction of Metabolic Pathways

Abstract: Prediction and reconstruction of metabolic pathways play significant roles in many fields such as genetic engineering, metabolic engineering, drug discovery, and are becoming the most active research topics in synthetic biology. With the increase of related data and with the development of machine learning techniques, there have many machine leaning based methods been proposed for prediction or reconstruction of metabolic pathways. Machine learning techniques are showing state-of-the-art performance to handle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…This innovative approach enables the inference of a new model for a closely related or phylogenetically linked species. It capitalizes on the correspondence between organisms to establish connections between metabolites across compartments through gene associations and reversible enzymatic reactions, as outlined in prior studies [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…This innovative approach enables the inference of a new model for a closely related or phylogenetically linked species. It capitalizes on the correspondence between organisms to establish connections between metabolites across compartments through gene associations and reversible enzymatic reactions, as outlined in prior studies [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…AI can help uncover hidden connections among diverse data fragments, thereby facilitating the extraction of crucial biological insights 36 . It has been demonstrated that AI models can successfully analyze complex omics data for diverse applications, such as the reconstruction of metabolic pathways 37 , drug discovery, and biomarkers 38,39 . Glycomics undoubtedly involves the deciphering process of hidden connections, especially given the ambiguity found in glycan structures (such as the non-template-directed, flexible, and repeating structural units available for a variety of modifications) and the various molecules that bind to glycans.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning approaches are effective in integrating prior information. However, its biological interpretability is limited ( Shah et al, 2021 ) and the performance is constrained by the sparsity of biological interactions. Also, due to the complexity of matrix operations, processing large-scale data is highly challenging.…”
Section: Introductionmentioning
confidence: 99%